Disputatiuncula de taedio, pavore, tristicia Iesu: Concio de immensa Dei misericordia ; Modus orandi Deum ; Explanatio symboli apostolorum sive catechismus ; De praeparatione ad mortem - Erasmus, Desiderius; Erasmus, Desiderius; Erasmus, Desiderius; Erasmus, Desiderius; Erasmus, Desiderius; Erasmus, Desiderius; O'Malley, John W.; Erasmus, Desiderius; Erasmus, Desiderius; Erasmus, Desiderius; Erasmus, Desiderius; Erasmus, Desiderius (Collected works of Erasmus Spiritualia and pastoralia, 1998)
Introduction / John W. O'Malley -- A short debate concerning the distress, alarm, and sorrow of Jesus / translated and annotated by Michael H. Heath -- A sermon on the immense mercy of God / translated and annotated by Michael J. Heath -- On praying to God / translated and annotated by John N. Grant -- An explanation of the Apostles' Creed / translated by Louis A. Perraud ; annotated by Laurel Carrington -- Preparing for death / translated and annotated by John N. Grant.